Strategi peningkatan keterampilan berenang siswa menggunakan metode pelatihan dan media - Sugiyanto, Fx.; Pangastuti, Nur Indah; Sujarwo, Sujarwo (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Many students find that swimming is a necessary skill, yet many struggle to learn the appropriate form due to inadequate teaching. Learning can happen faster with the right training media, and knowledge of swimming techniques can be improved. Innovative teaching methods and training media are needed to optimise students' mastery of swimming skills. This study is to assess how well proper workout regimens and media can enhance fundamental swimming skills. This study uses an action research design, where three action research cycles are (1) preparation, (2) action, (3) observation, and (4) reflection. If at least 75% of children can perform basic swim movements in a crawling style successfully, then this learning has been successful. This study used a percentage analysis methodology as its analytical method. While at least 75% of students who received a completeness score in swimming during the first cycle showed success in basic crawl style movements, the learning results of students' movements were not in accordance with the success indicators; only 55.55% of students achieved the overall target. The number of students who achieved the goal in the second cycle increased to 32 or 71.11%. At the end of the cycle, 40 students, or 88.89% of students, achieved the overall target. According to the study's findings, the basic swimming ability of adolescent students can be improved by using land exercises and training tools.